1997
DOI: 10.1148/radiology.202.2.9015091
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated hyperfractionation radiation therapy after lumpectomy and axillary lymph node dissection in patients with stage I or II breast cancer: pilot study.

Abstract: This breast-conservation accelerated hyperfractionation radiation therapy schedule is tolerable. Additional follow-up is necessary to determine long-term morbidity and cosmesis, and further study in a larger patient group is necessary to confirm efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…There was also no significant difference in late grade 3 or higher skin toxicity between the groups (2.1% vs. 0% respectively, p = 0.30) or in grades 1-2 toxicity (20.8% vs. 25.5% respectively, p = 0.69). Similarly, excellent or good cosmetic result scores were similar in both groups (p = 0.80) Current OnCOlOgy-VOlume 17, number 5 controlled trials in which hypofractionation was shown to achieve local control similar to that with standard fractionation [6][7][8][9] , without an increase in long-term side effects, this approach was adopted in several parts of the world, including Canada and the United Kingdom.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…There was also no significant difference in late grade 3 or higher skin toxicity between the groups (2.1% vs. 0% respectively, p = 0.30) or in grades 1-2 toxicity (20.8% vs. 25.5% respectively, p = 0.69). Similarly, excellent or good cosmetic result scores were similar in both groups (p = 0.80) Current OnCOlOgy-VOlume 17, number 5 controlled trials in which hypofractionation was shown to achieve local control similar to that with standard fractionation [6][7][8][9] , without an increase in long-term side effects, this approach was adopted in several parts of the world, including Canada and the United Kingdom.…”
Section: Resultsmentioning
confidence: 79%
“…Although this treatment scheme has been widely adopted, much debate remains about the ideal radiotherapy regimen to use. Several alternative fractionation regimens have recently been assessed 5 and compared with the standard fractionation schedule (25 fractions of 2 Gy each over 5 weeks) [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…The previous interesting clinical results are further investigated by considering the UL and the GL with different treatment schedules. In particular,since clinical experience confirms that highly proliferative tumors are unsatisfactorily treated by conventional RT schedule, we have performed simulations by assuming non-conventional, yet widely applied RT schedules, such as hyperfractionation [20], CHART protocol [21] and hypofractioned regimes [22], which are known to be more effective in controlling the evolution of highly proliferative tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Actually, clinical experience confirms that highly proliferative tumors are unsatisfactorily treated by conventional RT schedule. Simulations are therefore proposed by assuming non-conventional RT schedules such as accelerated hyperfractionation [20], CHART protocol [21] and hypofractioned regimes [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation